Replacement of wheat bran with spineless cactus in sugarcane-based diets for steers - Conceição,Maria Gabriela da (2016)
ABSTRACT The effect of replacing wheat bran with spineless cactus (0, 25, 50, 75, and 100%) in sugar cane-based diets on the intake of nutrients, feeding behavior, and rumen digestibility of steers was assessed using digested samples collected from the omasum. Five crossbred steers (1/2 Holstein-Zebu) were fitted with cannulas in the rumen and then assigned to a 5 × 5 Latin square design. Samples of omasal digesta were collected for three days. Rumen was evacuated via the rumen cannula to determine the rumen pool of dry matter (DM), neutral detergent fiber (NDF), indigestible NDF (iNDF), intake (ki), passage (kp) and degradation (NDF) rates, and the passage of iNDF (kpi). Nutrient intake displayed a quadratic effect, with maximum intakes of DM (5.73 kg d−1), non-fiber carbohydrates (NFC, 4.63 kg d−1), and digestible organic matter (DOM, 3.45 kg d−1) estimated at the replacement levels of 54.63, 60.00, and 43.17%, respectively. The replacement levels showed no effect on feeding, rumination, or idle times. There was a linear increase in the total apparent and ruminal digestibility of CP as the spineless cactus content in the diet was increased. There was no effect on total and partial digestibilities of OM and NDF or on intestinal digestibility of CP. No effect was observed on the rumen pool of DM, NDF, or iNDF. Furthermore, ki, kp, NDF degradation, and iNDF passage rates displayed a quadratic effect, with higher concentrations estimated for replacement levels of 56.07, 56.12, 59.00, and 55.20%, respectively. Replacing 55% wheat bran with spineless cactus in sugar cane-based diets is recommended.